2020
DOI: 10.1159/000506281
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Instrumental and Basic Activities of Daily Living Impairment in Older Adults with Very Mild Alzheimer’s Disease

Abstract: Background/Aims: Age-related changes in impairments in activities of daily living (ADL) in older adults with very mild Alzheimer's disease (vmAD) have been scarcely explored. We clarified the characteristics of ADL impairment and examined how ADL impairments differed by age in such patients compared with community-dwelling cognitively normal older adults. Methods: The participants were 107 older adults with vmAD (Mini-Mental State Examination [MMSE] score ≥24), all of whom were first-visit outpatients at the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Deterioration in these iADL becomes more apparent with age-related neurodegeneration such as mild cognitive impairment (MCI) and Alzheimer's disease (AD) (Jekel et al, 2015). Executive functions in particular are paramount in carrying out numerous iADL, but are also vulnerable to the effects of normal and pathological cognitive aging (Overdorp et al, 2016;Tabira et al, 2020). Working memory is one core executive function that relates to the ability to temporarily store, process, and manipulate the information necessary for higher order cognitive tasks such as decision making, learning, and reasoning (Baddeley, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Deterioration in these iADL becomes more apparent with age-related neurodegeneration such as mild cognitive impairment (MCI) and Alzheimer's disease (AD) (Jekel et al, 2015). Executive functions in particular are paramount in carrying out numerous iADL, but are also vulnerable to the effects of normal and pathological cognitive aging (Overdorp et al, 2016;Tabira et al, 2020). Working memory is one core executive function that relates to the ability to temporarily store, process, and manipulate the information necessary for higher order cognitive tasks such as decision making, learning, and reasoning (Baddeley, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In line with previous studies that concluded that memory or attention deficiencies are significant predictors of ADL dependency among older adults [50,51], our participants with memory or concentration problem were at higher odds of poor functioning. Severe memory deficits is one of the earliest and most pronounced symptoms of cognitive impairment related to Alzheimer's disease, which often causes ADL limitations in older adults [52]. An earlier study also suggested that attentional impairments may be driving impairment in ADL among older people [53].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature, there are highly significant age differences in food choice and consumption. 44 However, these items should be reexamined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the data of this study were gathered through personal interviews. As people tend to give more socially acceptable answers during face-to-face interaction than they might in other survey methods, 44 the results of the study should be interpreted carefully. As discussed above, the nutrition subscale required further scrutiny and revision to improve the PSIs and reliability.…”
Section: Discussionmentioning
confidence: 99%